2008
DOI: 10.1167/iovs.07-1531
|View full text |Cite
|
Sign up to set email alerts
|

Spectacle Acceptance among Secondary School Students in Rural China: The Xichang Pediatric Refractive Error Study (X-PRES)—Report 5

Abstract: Many families in rural China will pay for glasses, though spectacle acceptance was < 50%, even among children with poor vision. Acceptance could be improved by price reduction, education showing that glasses will not harm the eyes, and parent-focused interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
90
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(99 citation statements)
references
References 18 publications
8
90
1
Order By: Relevance
“…If a student had spectacles but was not wearing it, the student was considered as "non-compliant". Children not wearing glasses were asked whether they had the eyeglasses with them and to identify 1 of 10 different reasons for noncompliance, which had been identified from other researches (1)(2)(3)(4)(5)(6)(7) as the most common reasons for spectacle noncompliance in school children.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…If a student had spectacles but was not wearing it, the student was considered as "non-compliant". Children not wearing glasses were asked whether they had the eyeglasses with them and to identify 1 of 10 different reasons for noncompliance, which had been identified from other researches (1)(2)(3)(4)(5)(6)(7) as the most common reasons for spectacle noncompliance in school children.…”
Section: Methodsmentioning
confidence: 99%
“…The dictionary (The Oxford Concise Dictionary) meaning of compliance refers to "Obedience to a request or command", in respect to our study, we used to prescribe for spectacles but it is useful only at time when child patients are wearing them. Refractive errors are commonly found as the causative agent for visual impairment in the most surveyed population and this impairment is easily treatable (1)(2)(3)(4)(5)(6)(7) . Previous studies shows prevalence of refractive error differs with geographic location, age, gender, education level, and amount of near work (1)(2)(3)(4)(5)(6)(7) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 However, programs in China, 3 Mexico, 6 and Africa 7 have reported poor compliance with free spectacles, with rates of observed, short-term wear at unannounced visits ranging from 13% to 41%. Factors limiting wear of glasses include discomfort or inconvenience, 6,8 concerns over being teased, 6,9 parental opposition, 6,10,11 lack of perceived need, 6,[8][9][10] and fear of damage to the eyes [8][9][10][11] (though a trial 4 has now demonstrated that spectacle wear is in fact protective against age-related declines in uncorrected visual acuity among children). Previous randomized trials of specially designed educational interventions promoting spectacle wear aimed at children, teachers, and parents have demonstrated very modest 3 or no 12 impact on observed use of glasses among children at unannounced follow-up visits.…”
mentioning
confidence: 99%